History of the Language Sciences : an International Handbook on the Evolution of the Study of Language from the Beginnings to the Present. - Krner, E. F. K. (Walter de Gruyter, 2006)
Writing in English, German, or French, more than 300 authors provide a historical description of the beginnings and of the early and subsequent development of thinking about language and languages within the relevant historical context. The gradually emerging institutions concerned with the study, organisation, documentation, and distribution are considered as well as those dealing with the utilisation of language related knowledge. Special emphasis has been placed on related disciplines, such as rhetoric, the philosophy of language, cognitive psychology, logic and neurological science.